MEASURING STRATEGIC SUCCESS: A DESCRIPTIVE STUDY ON BALANCED SCORECARD ADOPTION AND FIRM OUTCOMES - NRKS Chakravarthy; Dr. Mahesh Chandra (International Journal of Data Science and IoT Management System, 2023)
Balanced Scorecard (BSC) has become one of the strategic management tools, which incorporates both financial and non financial performance indicators to align organizational activities with long term objectives. This paper will consider how the Balanced Scorecard has been adopted by firms and how it affects the organizational results. Primary data that were used was through structured questionnaires and a sample of managers and executives in various industries using a descriptive research design. The paper will discuss the level of BSC adoption, the key success outcomes that determine its adoption and the perceived positive impact on the performance of the firms in terms of financial outcomes, operational efficiency and alignment of the company strategic direction. The results indicate that those organizations that have transferred to the Balanced Scorecard report have increased clarity of strategy, improved performance monitoring and decision making. Besides, contextual factors like support to change leadership, organization culture and technological preparedness have immense influence on successful adoption. The research also offers practical evidence to managers and practitioners who are interested in using BSC as a strategic instrument and the challenges and advantages of its use.